Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Samudera Sarana Terminal Indonesia - Cahyani Prasetiawati; M. Akbar (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The sample in this study were all employees of PT Samudra Sarana Terminal totaling 41respondents with non-probability sampling with saturated sampling. The type of data used in thisstudy was obtained from primary data and secondary data. Data collection methods used,literature study and questionnaires. Data analysis techniques used in This study tested the validity,reliability, classic assumption test, multiple linear regression, and hypothesis testing. Researchresult. Partially compensation has a positive effect on employee performance because it is seenfrom the t-count value of 2.119 while the statisticaltable (t-table) is 2.022 and the compensationvariable significance value is 0.041 which is smaller than 0.05. So it can be concluded that H0 isrejected and Ha is accepted, this shows that partially compensation has a positive effect onemployee performance. The second result is that discipline has a positive effect on employeeperformance because it is seen from the t-count value of 2.142 while the table statistic (t-table) is2.022 and the Discipline variable's significance value is 0.039 which is smaller than 0.05. So it canbe concluded that H0 is rejected and Ha is accepted, this shows that partially Discipline has apositive effect on employee performance. The results of the third study, namely that simultaneouslyfor the Compensation and Discipline variables obtained Fcount = 5.654 and Ftable 3.24 and thesignificance value is 0.007 less than 0.05, so Ho is rejected and Ha is accepted. This shows thatjointly Compensation and Discipline have an effect on Employee Performance.